RICE FOOD SUPPLY CHAIN MANAGEMENT IN TOJO UNA-UNA DISTRICT - Almubrak, Moch. Riski; Miru, Sulaeman; Shamsuddin; Asngadi; Darman (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
The aim of this research is to describe the rice supply chain model in Tojo Una-Una Regency and look at the price margin from the initial supply chain process to the consumer as the final supply chain in its management. The research was conducted for 3 months. The method used was qualitative descriptive using a survey approach. The research was conducted in Tojo Una-Una Regency. The collection method was carried out by in-depth interviews. Data analysis was conducted using qualitative descriptive analysis assisted by supply chain management analysis. The research results show that; The supply chain model in Tojo Una-Una Regency is quite long and involves at least nine supply chain models, the highest profit is for the miller with a total of Rp. 6,400-Rp. 6,600 and the majority of the rice food price margin is around Rp. 11,000 to IDR 15,000 per kilogram, with the price per 50 kg bag from the South Sulawesi area, IDR. 495,000 to Rp. 510,000. For food from the Parigi Moutong area the price is Rp. 600,000 per bag, while food from the Banggai area is Rp. 590,000 per bag. With a selling price to consumers of IDR 530,000 to IDR 550,000 per 50 kg sack for rice from the South Sulawesi region. Meanwhile, rice from the Parigi and Banggai areas are priced at IDR 620,000 to IDR 630,000.